Raptor community composition in the Texas Southern High Plains lesser prairie‐chicken range - Adam C. Behney; Clint W. Boal; Heather A. Whitlaw; Duane R. Lucia (Wildlife Society Bulletin)
Abstract Predation can be a factor in preventing prey population growth and sustainability when prey populations are small and fragmented, and when predator density is unrelated to the density of the single prey species. We conducted monthly raptor surveys from February 2007 to May 2009 in adjacent areas of the Texas Southern High Plains (USA) that do and do not support lesser prairie‐chickens (Tympanuchus pallidicinctus), a candidate for protection under the Endangered Species Act. During the summer period corresponding to prairie‐chicken nesting and brood‐rearing, Swainson's hawks (Buteo swainsoni) were the most abundant raptor. During the lekking and overwintering period, the raptor community was diverse, with northern harriers (Circus cyaneus) being the most abundant species. Raptor abundance peaked during the early autumn and was lowest during the spring. Utility poles were a significant predictor of raptor density at survey points and Swainson's hawks and all raptors, pooled, were found in greater densities in non‐prairie‐chicken habitat dominated by mesquite (Prosopis glandulosa). Avian predation risk on prairie‐chickens, based on presence and abundance of raptors, appears to be greatest during winter when there is a more abundant and diverse raptor community, and in areas with utility poles. Published 2012. This article is a U.S. Government work and is in the public domain in the USA.